2000
DOI: 10.1046/j.1365-2702.2000.00412.x
|View full text |Cite
|
Sign up to set email alerts
|

The nursing care of stroke patients in nursing homes. Nurses’ descriptions and experiences relating to cognition and mood

Abstract: Registered nurses working in nursing homes often care for stroke patients with impaired cognition and mood disorders. Understanding the behaviour of these patients often puts great demands on nurses. This study illuminates registered nurses' descriptions and experiences of stroke patients and the nursing care given in nursing homes, with a focus on cognition and mood. Registered nurses responsible for the care of stroke patients in nursing homes were asked to describe the individual patient's state of health a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 35 publications
(45 reference statements)
0
22
0
Order By: Relevance
“…A lack of coordinated and standardised care for stroke survivors was highlighted by Stolee et al to be lacking in a LTC facility, resulting in suboptimal care for the specialised needs of these residents [32]. Another study reported the deficiency of focused and specialised care for stroke survivors demonstrated by nurses from five nursing homes, who experienced uncertainty regarding understanding stroke survivors and providing appropriate nursing care [35]. Further education in stroke care was requested by nursing staff taking care of stroke survivors in two studies [35,36].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A lack of coordinated and standardised care for stroke survivors was highlighted by Stolee et al to be lacking in a LTC facility, resulting in suboptimal care for the specialised needs of these residents [32]. Another study reported the deficiency of focused and specialised care for stroke survivors demonstrated by nurses from five nursing homes, who experienced uncertainty regarding understanding stroke survivors and providing appropriate nursing care [35]. Further education in stroke care was requested by nursing staff taking care of stroke survivors in two studies [35,36].…”
Section: Resultsmentioning
confidence: 99%
“…Another study reported the deficiency of focused and specialised care for stroke survivors demonstrated by nurses from five nursing homes, who experienced uncertainty regarding understanding stroke survivors and providing appropriate nursing care [35]. Further education in stroke care was requested by nursing staff taking care of stroke survivors in two studies [35,36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Nurses have reported that caring for patients with depression and cognitive impairment is difficult because of the complexity such patients present and a lack of specialist preparation. 27,28 Similarly, the difficulties that nurses face caring for patients with aphasia have been investigated and recommendations made to develop strategies to enhance communication. 29 -31 Existing methods of assessing patients' needs 32 and quality of life 33 were found to be problematic, with current practice not matching patients concerns.…”
Section: Acute Carementioning
confidence: 99%
“…2001), rehabilitation settings (Kirkevold 1997, O'Connor 2000), community settings (Forster & Young 1996, Dowswell et al. 1997), and long‐term care (Kumlien & Axelsson 2000). In these studies, however, the nursing interventions have not been clearly articulated or have been described only in broad terms, with no detail of the specific interventions.…”
Section: Strokementioning
confidence: 99%